Effect of ultrasound on nonsteroidal anti-inflammatory drugs complexed with copper, iron, zinc and graphene oxides - L. A. Mikhnavets; A. N. Tkach; U. S. Fiadosenka; D. V. Radziuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This work aims at the formation of nanocomposites based on graphene and metal oxides (copper-iron, zinc and iron) through ultrasonic interaction (20 kHz) and investigation of their electromagnetic properties by scanning electron microscopy, Raman and absorption spectroscopy, and fluorescence methods. The output of this work implies the development of a single-step ultrasound method to form functional Cu/Fe-, ZnO-and Fe3O4-polyvinyl alcohol nanocomposites, and the ultrasonic conjugation of these nanocomposites with pristine drugs, such as ketorolac and acetylsalicylic acid. We established that formed Cu/Fe-graphene-ketorolac, ZnO-grapheneacetylsalicylic acid and Fe3O4-ketorolac obtain optical and superparamagnetic properties of nanoparticles with improved electromagnetic characteristics due to ultrasonic conjugation. Cu/Fe-graphene-ketorolac nanocomposites are revealed to have a spherical shape (< 100 nm) and acquire improved optoelectronic properties due to copper and iron atoms in the matrix of graphene. It is demonstrated that ZnO-graphene-acetylsalicylic acid nanocomposites obtain properties of fluorescence mainly for electromagnetic interaction with the ZnO phase formed on the surface of graphene. Ultrasonic conjugation of ketorolac with magnetite proved to increase the electron density of Fe3O4-ketorolac that obtains superparamagnetic properties, and its biocompatibility can be improved when coated with polyvinyl alcohol. In general, formed nanocomposites are of great interest in medical electronics and nanomedicine as functional materials with electromagnetic properties being controlled at the molecular and atomic levels. Such nanocomposites can also find application as components in electronic devices for diagnosis and treatment of serious inflammatory disorders. Industries will find the singlestep ultrasound method of special interest because it is eco-friendly and can be scaled up by a versatile spectrum of inorganic and organic materials and drugs.